Analisis Risiko Kos-Kosan dengan Pendekatan ISO 31000: (Studi Kasus: Usaha Kos Jl. Babakan Wadana, Kecamatan Rancasari, Kota Bandung) - Shabrina Nurhiyan Nisa; Hani Humaeriyah (Indo Publishing, 2026)
The expansion of small-scale residential property sectors in Indonesia presents promising investment opportunities yet necessitates comprehensive evaluation to ensure business sustainability. This research aims to analyze business feasibility and manage risk for Rancasari boarding house, Bandung, which operates 6 rooms at Rp 500,000 rental rate per room using sequential explanatory mixed method approach. Feasibility evaluation was conducted through market, technical, legal, and financial aspects analysis employing Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period, and Break Even Point (BEP) methods, while risk management implemented ISO 31000:2018 framework encompassing identification, analysis, evaluation, and risk treatment. Research findings indicate very high feasibility level with tenant perception score of 4.25, break-even point achieved at 33% occupancy rate, and annual revenue projection of Rp 36,000,000 with capital recovery period of 15-20 years. Risk identification generated seven categories with two high-priority risks namely social resistance from surrounding residents and market competition from competitors requiring mitigation strategies through local community involvement, tenant screening system, and periodic facility maintenance. This research contributes theoretically to integration of feasibility study with international standard-based risk management and provides applicable evaluation model for property sector MSMEs to enhance resilience and competitiveness amid market uncertainty